Pectin methyl esterases and rhamnogalacturonan hydrolases: weapons for successful Monilinia laxa infection in stone fruit?. (9th June 2019) - Baró‐Montel, N.; Vall‐llaura, N.; Usall, J.; Teixidó, N.; Naranjo‐Ortíz, M. A.; Gabaldón, T.; Torres, R.
Abstract : The secretion of cell wall‐degrading enzymes is one of the mechanisms used by necrotrophic fungi to colonize host tissues. However, information about virulence factors of Monilinia spp., the causal agents of brown rot in stone fruit, is scarce. Plant cell walls have three main components that are broken down by fungal enzymes: cellulose, hemicellulose and pectin. In order to identify Monilinia laxa candidate proteins involved in pectin hydrolysis, two in vitro approaches were conducted: (i) phenotypic and ecophysiological characterization of growth of the pathogen at different pHs, in glucose‐ and pectin‐containing solid media for 7 days' incubation; and (ii) expression analysis of genes encoding M. laxa pectin methyl esterases ( MlPME s) and rhamnogalacturonan hydrolases ( MlRG‐HYD s) after incubation for 0.5, 2, 6, 24 and 48 h in glucose‐ and pectin‐containing liquid media. Phenotypic tests showed the role of carbon source on M. laxa growth rate and aggressiveness, and indicated that pectinases were greatly affected by pH. Gene expression analyses uncovered differences among members of each family of pectinases and between the two families, defining sets of genes expressed at earlier (0.5–6 h) and later (48 h) phases. Notably, the up‐ or down‐regulation of these target genes was carbon source‐dependent. Finally, an in vivo study confirmed the synergistic and complementary role that these genes play in the M. laxa– stone fruit pathosystem. Based on these results, it is hypothesized that MlPME2, MlRG‐HYD1 and MlRG‐HYD2 may be potential virulence factors of M. laxa in the process from infection to colonization.